2022
DOI: 10.1108/apjml-01-2021-0066
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between needs, motivations and information sharing behaviors on social media: focus on the self-connection and social connection

Abstract: PurposeThe purpose of this study is to investigate the factors that influence the information sharing behavior of individuals on social media. Furthermore, the study analyzes the effect that individuals’ self-connection to social media has on information sharing through self-efficacy and the effect of social-connection on information sharing through empathy.Design/methodology/approachA survey questionnaire was developed and distributed to social media users from general participants in the Republic of Korea. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The concrete construct in the present study representing the concept of the social value of sharing is the sense of connectedness, which refers to the extent to which consumers believe sharing something with others can make them feel connected with those people and the community and thus increase their overall sense of belonging. Research has shown that sharing information and experiences not only on social media (e.g., Kim et al, 2023) but also through a sharing service (e.g., Baek & Oh, 2021; Hawlitschek et al, 2018) contributes to increased social connections and a broadened community.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The concrete construct in the present study representing the concept of the social value of sharing is the sense of connectedness, which refers to the extent to which consumers believe sharing something with others can make them feel connected with those people and the community and thus increase their overall sense of belonging. Research has shown that sharing information and experiences not only on social media (e.g., Kim et al, 2023) but also through a sharing service (e.g., Baek & Oh, 2021; Hawlitschek et al, 2018) contributes to increased social connections and a broadened community.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Overall, social connectedness is an important inner concept that strengthens the effects of individuals' social roles [85,86], because it elicits a sense of self-worth in the group and enhances the desire for additional connection with others [17]. Indeed, Gieling and Ong (2016) demonstrated that social connectedness enables individuals to identify strongly with their group members and drives identity-enhancement motivation [87].…”
Section: The Moderating Effect Of Social Connectednessmentioning
confidence: 99%
“…There is also self-interest behavior when the user is promised to give a certain degree of reward to the user for sharing out [5]. The second type of motivation is sharing involving others, such as when the user feels that the content shared is beneficial to others, and sharing can help the user connect and strengthen interpersonal relationships [6].…”
Section: Introductionmentioning
confidence: 99%